Pharmacokinetics and Withdrawal Times of Ampicillin in Ducks - Poapolathep, Amnart; Limpoka, Malinee; Tansakul, Natthasit; Phaochoosak, Napasorn; Klangkaew, Naruamol; Passadurak, Wanida (Agriculture and Natural Resources, 2001)
Pharmacokinetics of ampicillin (APC) was investigated in ducks after drug administration at a single dose rate of 20 mg/kg body weight by intravenous (i.v.), intramuscular (i.m.), subcutaneous (s.c.) and oral (p.o.) routes. A two-compartment pharmacokinetic model was developed to describe the fate and disposition of this drug. Mean peak plasma concentrations of APC was 10.52 ± 2.06, 12.21 ± 0.66, 5.62 ± 0.95 and 1.61 ± 0.20 microgram/ml after i.v., i.m., s.c. and p.o. administration respectively. Ampicillin was shown to have an elimination half-life (t1/2β) of 97 ± 9.55 min, while the elimination rate constant (Kel ), the apparent volume of distribution (Vd(area)), and the total body clearance (ClB) were 2.09 ± 0.07 h-1, 1.79 ± 0.41 L/Kg and 1.21 ± 0.19 L/Kg/h respectively. In addition, the bioavailability following different routes were 91.11 ± 7.2 % for i.m., 62.22 ± 8.03 % for s.c. and 17.78 ± 2.08 % for p.o. administration. The results suggested that when treating ducks, the pharmacokinetic behaviors of amipicillin should be considered in order to optimize the therapeutic dose, and to allow the preslaughter withdrawal time and maximum residue limits of ampicillin for duck.